REVITALISASI PERMAINAN TRADISIONAL KASEDE-KASEDE BERBASIS KEARIFAN LOKAL SEBAGAI MEDIA PENGUATAN PENDIDIKAN KARAKTER SISWA DI SD NEGERI 1 BUNGI - Suhendro Gusli; La Ali; Muh. Ilham Hafid; La Rodi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The massive development of digital technology has shifted the existence of traditional games and triggered character degradation in children, such as individualism and reduced empathy. This study aims to describe the revitalization process of the traditional game Kasede-Kasede as a medium for strengthening local wisdom-based character education for students at SD Negeri 1 Bungi. The research method used was descriptive qualitative. The research subjects included the principal, teachers, and fourth and fifth grade students. Data collection was conducted through participatory observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the revitalization of the Kasede-Kasede game was carried out through three stages: reconstruction of the game rules, integration into co-curricular/extracurricular activities, and routine practice. The character values ​​successfully strengthened through this game include cooperation (gotong royong), honesty (integrity), discipline, emergency response (empathy), and sportsmanship. The success of this implementation was supported by student enthusiasm and school commitment, despite the challenge of limited suitable play space. This study concludes that the Kasede-Kasede game is an effective contextual educational tool for developing superior character in elementary school students.